Management of Geriatric Anesthesia on Emergency Surgery - Achmad Hariyanto; Isngadi Isngadi (Journal of Anaesthesia and Pain, 2021)
In geriatric patients, emergency surgery is more common than elective surgery. The incidence of medical complications increases along with aging while the rate of surgical complications remains constant. Postoperative complications escalates short-term morbidity and mortality and also associated with decreasing long-term survival. The main purposes of geriatric patients' care were to maintain hemodynamics, speed up recovery, and perform an assessment to avoid any further decline in functional capacity. The choice of anesthesia and how to administer anesthesia agents should be adjusted for the geriatric patient.